2008
DOI: 10.1017/s0014479707005935
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Impacts of Participatory Research

Abstract: Farmer participation in agricultural research can improve the efficiency and impact of the research. This functional component of participatory research includes the identification of traits that guide crop breeders' work. Participatory research can also lead to farmer empowerment, although when carried out by research organizations, direct empowerment is often limited to relatively few farmers. Farmer empowerment is, therefore, best carried out by development organizations whose longer-term interaction with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
(41 reference statements)
2
40
0
Order By: Relevance
“…Secondly, and related to the first, participants can develop an appreciation for the knowledge held by different social groups -and for those groups themselves (Faridah et al 2017, this issue) by engaging in inter and intra-group interactions, identifying common concerns that foment community cohesion (Hellin et al 2008). Thirdly, together these processes can inspire local change by motivating a shared sense of social responsibility and collective action (Jones et al 2014).…”
Section: The Contact Zones Of Participatory Researchmentioning
confidence: 99%
“…Secondly, and related to the first, participants can develop an appreciation for the knowledge held by different social groups -and for those groups themselves (Faridah et al 2017, this issue) by engaging in inter and intra-group interactions, identifying common concerns that foment community cohesion (Hellin et al 2008). Thirdly, together these processes can inspire local change by motivating a shared sense of social responsibility and collective action (Jones et al 2014).…”
Section: The Contact Zones Of Participatory Researchmentioning
confidence: 99%
“…If the research project is designed in a university or research institution that is less responsive to the existing problems of smallholder agriculture, it is unlikely that researchers would have the freedom to adopt participatory approaches and to respond to farmers' needs and priorities when carrying out the research. The same applies to participatory research projects that are carried out in countries or regions with a long history of supply-driven agricultural research and where the flow of information and technology is linear from researchers via extension agents to farmers (Biggs 1990;Neef 2005;Hellin et al 2008 …”
Section: Id Institutional Context Of the Research Projectmentioning
confidence: 99%
“…Pretty 1995;Lilja and Bellon 2008). Today, most practitioners of participatory agricultural research emphasize a more functional role of participation (Hellin et al 2008), although the question of power relations in participatory approaches is still of great relevance, particularly when the research project focuses on marginalized groups, e.g., women, ethnic minority groups or the poor. Incorporating stakeholders in the research process often has an impact on social capital formation.…”
Section: Vid Empowerment and Social Capitalmentioning
confidence: 99%
“…Hellin et al (2008) suggested that the use of participatory approaches is one way to enhance rural innovation capacity, where such approaches may involve increased accessibility by farmers to externally developed technology, the joint development of relevant and appropriate technology by farmers and scientists, or the enhancement of local capacity to address problems and devise solutions. Hoffmann et al (2007) argued that the PRE approach may yield many innovations and new kinds of knowledge because farmers have far more opportunities than researchers for experimentation under different cultural and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%